2019
DOI: 10.4236/wjet.2019.72021
|View full text |Cite
|
Sign up to set email alerts
|

Study on Productivity Model of Herringbone-Like Laterals Wells and Optimization of Morphological Parameters Considering Threshold Pressure Gradient in Heavy Oil Reservoirs

Abstract: Compared with conventional well, herringbone-like laterals wells can increase the area of oil release, and can reduce the number of wellhead slots of platforms, and also can greatly improve the development efficiency. Based on threshold pressure gradient in heavy oil reservoir, and the applied principle of mirror reflection and superposition, the pressure distribution equation of herringbone-like laterals wells is obtained in heavy oil reservoir. Productivity model of herringbone-like laterals wells is propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Their findings indicated that wells were more productive when branches were positioned nearer to each other. Sun et al [17] also observed that as the distance between branches grew, interference between them diminished. Ouadi et al [13] found that increasing branch gaps led to reduced reservoir volume and a minor flow rate drop (Figure 10).…”
Section: Distance Between Adjacent Branchesmentioning
confidence: 95%
See 4 more Smart Citations
“…Their findings indicated that wells were more productive when branches were positioned nearer to each other. Sun et al [17] also observed that as the distance between branches grew, interference between them diminished. Ouadi et al [13] found that increasing branch gaps led to reduced reservoir volume and a minor flow rate drop (Figure 10).…”
Section: Distance Between Adjacent Branchesmentioning
confidence: 95%
“…Their findings indicated that wells were more productive when branches were positioned nearer to each other. Sun et al [17] also observed that as the distance between branches grew, interference between them diminished.…”
Section: Distance Between Adjacent Branchesmentioning
confidence: 95%
See 3 more Smart Citations